Language development in bilingual returnees - Flores, Cristina (2019)
The present chapter discusses language development in bilingual returnees, that is second or third generation ex-migrants, who have lived for an extended period in a migration context and have, at some point in their life, returned to their (or their parents’) country of origin. The return to the homeland comes along with a significant shift in the returnees’ input conditions, which allows discussing two different dimensions of this particular bilingual population. On the one hand, research on returnees allows investigating the effects of loss of contact with the ex-environmental (dominant) language. On the other hand, this population experiences increasing exposure to the heritage language (back in the homeland), giving valuable insights to heritage language development in an input setting that is still understudied